The Sera levels of Interleukin-13 in Patients with Atopic Dermatitis in Thi-Qar province - Amel A. Naji; Hind M Mousa (University of Thi-Qar Journal of Science, 2022)
The Interleukin-13 (IL-13) is a component of the innate immune system that is primarily produced by Th2 cells and is found in high concentrations in skin lesions of atopic dermatitis. The study comprised 90 people of both genders, 45 of whom were patients who attending to Al-Nassirya teaching Hospital, Dermatology, during a period between November 2021 to March 2022, and the same number served as controls. Blood samples were obtained from both groups, and the serum levels of IL-13 were estimated using an ELISA-ready kit.The findings of the current study referred that young adult, and the females gender were as more effective in Atopic Dermatitis, andthe female to male ratio was 1.14: 1. On the other hand, the results indicated there were elevated sera levels of IL-13 in AD patients in contrast to the controls group. Also, there is no significant difference in IL-13 sera levels among patients groups regarding to severity of AD P˃0.05). we concluded from a significant difference between the healthy control group and patients that IL-13involved in the pathogenesisof AD